Особливості управління транскордонними екосистемами на прикладі Люблінського воєводства - Скороход, Ірина Святославівна; Олейник, Вікторія Василівна; Skorokhod, Iryna S.; Oleinyk, Viktoriia V. (Східноєвропейський національний університет імені Лесі Українки ; Рада Центрально-Східного регіону незалежної самоврядної професійної спілки "Солідарність", 2013)
У статті досліджено особливості існування транскордонних екосистем в рамках Єврорегіону «Буг». Визначено поняття «транскордонна екосистема», та елементи транскордонності таких видів ресурсів, тобто випадки, коли екосистема набуває статусу транскордонної. У статті подаються особливості управління транскордонними екосистемами в межах Люблінського воєводства Польщі: вирубка, заготівля деревини, лісовідновлення та лісорозведення, охоронювані природні території тощо. Розглядається перший стратегічний документ в галузі транскордонної співпраці прикордонних територій Польщі, України та Білорусії – Стратегія «Три Полісся» – спільна стратегія охорони i екологічного використання природничої спадщини теренів польсько-білорусько-українського прикордоння».

The features of transboundary ecosystems existence within the Euroregion “Bug” are studied in the parer. The concept of “transboundary ecosystem” and transboundary elements of these kinds of resources, namely the cases when the ecosystem acquires the status of transboundary are determined. It is noted that the establishment of transboundary parks, green corridors, nature reserves contributes to the more effective transboundary management, research and monitoring, brings the economic benefits to national economies and provides better management of transboundary problems such as fire, pests, poaching, pollution, smuggling and so on. The peculiarities of transboundary ecosystems management within the Lublin Voivodeship of Poland are submitted in the parer: deforestation, logging, reforestation and afforestation, protected natural areas and so on. The first strategic documents relating to trans-border cooperation of the borderland areas of Poland, Ukraine and Belarus – The strategy “Three Polessyes – a common strategy of preservation and ecological use of the natural heritage of the Belarusian-Polish-Ukrainian borderland” is considered.
The features of the transboundary ecosystems management an example of Lublin Voivodeship
Keywords: Єврорегіон «Буг»; Euroregion “Bug”; транскордонна екосистема; transboundary ecosystem; стратегія «Три Полісся»; the strategy “Three Polessyes”